1989
DOI: 10.1136/thx.44.8.678
|View full text |Cite
|
Sign up to set email alerts
|

Locally invasive pulmonary aspergillosis occurring in a gardener: an occupational hazard?

Abstract: Fatal locally invasive pulmonary aspergillosis occurred in a previously fit young patient who had no predisposing factors other than exposure to fungal spores in his occupation as a gardener.Invasive pulmonary aspergillosis is uncommon, usually occurring in immunocompromised patients or in those with abnormal lungs. We describe a fatal case occurring in a previously fit young man.Case report A 34 year old man was admitted as an emergency with a five day history of dyspnoea, unproductive cough, fever, and anore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…The features of this patient's presentation and her course are similar to other cases in the literature in which presumed immunocompetent individuals initially present with hyper-IgE, eosinophilia (of blood, tissue, or BAL), often after massive exposure and then, either simultaneously or subsequently, develop an IPA characterized by suppurative granulomas within the parenchyma of the lung [9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The features of this patient's presentation and her course are similar to other cases in the literature in which presumed immunocompetent individuals initially present with hyper-IgE, eosinophilia (of blood, tissue, or BAL), often after massive exposure and then, either simultaneously or subsequently, develop an IPA characterized by suppurative granulomas within the parenchyma of the lung [9][10][11][12][13][14].…”
Section: Discussionsupporting
confidence: 74%
“…Finally, ZUK et al [14] reported the case of a previously healthy gardener aged 34 yrs who presented with a 5 day history of dry cough, fever, and dyspnoea. A chest radiograph revealed bilateral basal infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…One case was organic dust toxic syndrome (ODTS), one case was insufficiently characterized (hypersensitivity pneumonitis or ODTS), one case was external otitis from Aspergillus niger, and three were invasive aspergillosis (Bünger et al, 2007;Clark et al, 1984;Weber et al, 1993). The latter cases concerned a worker in a green-waste composting plant, a professional gardener that probably handled compost, and a welder who spread rotting tree and plant mulch from a sack around his garden (Russell et al, 2008;Vincken and Roels, 1984;Zuk et al, 1989). The three cases of invasive aspergillosis did not represent typical characteristics for individual risk factors because the patients were not known to be immuno-compromised.…”
Section: Resultsmentioning
confidence: 99%
“…These patients were either agricultural or manual workers in ''moldy'' environments. In another report from the UK, fatal locally invasive pulmonary aspergillosis occurred in a previously healthy young patient who had no predisposing factors other than exposure to fungal spores in his occupation as a gardener [25].…”
Section: Professions Associated With Ifis Secondary To Inhalation Of mentioning
confidence: 98%